Study of Optimal Biodiesel Production from Waste Frying Oils for Community, and Prototype of Biodiesel Reactor Using Biomass Energy - Sopajarn, Arrisa; Jitjamnong, Jakkrapong; Kasetsomboon, Naparat; Niseng, Suhdee (Recent Science and Technology, 2023)
This research aimed to examine biodiesel synthesis from waste of Khaoroopchang Municipality, Songkhla Province. Waste cooking oil with acid value less than 2 mgKOH/g collected from markets was used. The four parameters: molar ratio of alcohol to oils (3:1-15:1), amount of catalyzed (1-5 %wt.), reaction time (min), reaction temperature (50-70 °C), and impeller speed (300 rpm) were investigated. The response surface methodology with central composite design (CCD) was adopted to optimize the condition of base-catalyzed transesterification in lap-scale. The result indicated that under condition of 7.73:1 of molar ratio of alcohol to oils, 3.97 %wt. of KOH, 60.54 min of reaction time, and 55 °C of reaction time, biodiesel purity was obtained comparably for commercial biodiesel standard. Then the data in lap-scale were used for studying biodiesel production system for community from waste frying oils by using biomass energy for heating the reaction. After testing the system with the same optimized condition in lab-scale, methyl ester purity was achieved 96.83 wt.%. This biodiesel was suitable for using in agricultural engine and diesel engine for long-tailed fishing boat.